THE RELATINSHIP BETWEEN ANEMIA AND CHRONIC ENERGY DEFICIENCY (CED) IN PREGNANT WOMEN AND THE INCIDENCE OF LOW BIRTH WEIGHT (LBW) IN THE WORKING AREA OF ARJASA COMMUNITY HEALTH CENTER - Riskiyatun Nikmah; Ainul Hidayati (Journal of Nursing Periodic, 2026)
or Infant Mortality Rate (IMR) where the cases always increase every year compared to other developing countries. Low Birth Weight (LBW) babies have a smaller chance of survival and are more susceptible to disease until adulthood. One of the factors that can cause LBW is maternal Hb (Hemoglobin) below 11 g / dl and KEK with LILA below 23.5 cm Methods: The type of observational analytical research with a cross-sectional design and a retrospective approach using research instruments in the KIA book, where each research subject is only observed once, and measurements of independent variables and dependent variables are carried out at the same time. The population in this study was 62 with inclusion criteria of mothers who have babies under one year old, have a KIA book, and are willing to be respondents. With the sampling technique using the total sampling technique. Results: Shows that most respondents did not experience anemia during pregnancy as many as 33 respondents (53.2%) in the KEK category most did not experience KEK during pregnancy as many as 38 respondents (61.3%) and in the LBW category most did not experience LBW during delivery as many as 42 respondents (67.7%). From the results of the Chi-Square analysis of anemia with LBW, a p-value (0.533)> (0.05) was obtained, so it can be concluded that H0 is accepted and Ha is rejected, which means there is no relationship between anemia and the incidence of LBW and from the results of the KEK analysis with LBW, a p-value (0.672)> (0.05) was obtained, so it can be concluded that H0 is accepted and Ha is rejected, which means there is no relationship between KEK and the incidence of LBW Discussion: : Anemia in pregnant women and KEK does not directly affect the incidence of LBW, there are several other factors that influence it, namely maternal age, ANC visits, and consumption of Fe tablets and nutritious food